Investigation of Campylobacter jejuni and Campylobacter coli isolated from broilers susceptibility to antibiotics - Tambur, Zoran; Vukovic, Branislava; Doder, Radoje (Veterinarski glasnik, 2015)
In this work sensitivity to eritromycine, tetracycline and ciprofloxacin was investigated on 16 (sixteen) strains Campylobacter jejuni and Campylobacter coli originated from broilers? coecum by use of dics-diffussion method and E-test. Out of 10 (ten) examined strains of C. jejuni, 1 strain (10%) was resistant to erithromycin, 5 (five) examined strains (50%) to tetracycline and 4 (four) examined strains (40%) to ciprofloxacine. Out of 6 investigated strains of C. coli, 1 strain was resistant to erithromycin (16,7%), 5 of investigated strains to tetracycline and ciprofloxacine (83,3%) (table 1 and 2, graph 3). Out of 16 (sixteen) investigated strains of C. jejuni and C. coli, 9 (nine) strains were resistant to ciprofloxacine (56,2%), 2 (two) strains to erythromycine (12,5%) and 10 of investigated strains to tetracycline (62,5%). nema